Enhanced Catalytic Activity with Oxygen for Methyl Acrylate Production via Cross‐Aldol Condensation Reaction. Issue 7 (9th May 2018) - Zuo, Cuncun; Ge, Tingting; Wang, Gang; Guo, Xinpeng; Li, Chunshan; Zhang, Suojiang
Abstract: An innovative technology for the production of methyl acrylate via vapor‐phase cross‐aldol condensation is described. Catalytic process intensification was realized through the enhanced catalytic activity with oxygen by catalyst design and adjustment of active sites. Crystal phases with different V valences in vanadium phosphate catalysts were controllably synthesized in the presence of oxygen. Donating electron and withdrawing electron sites arose when oxygen moved from one crystalline phase to another, just for the α ‐H removal of methyl acetate and formaldehyde protonation. The reaction pathway and transition states were confirmed via molecular simulation with quantum chemistry theory. The catalytic activity was evaluated in a fixed‐bed reactor by adjusting the percentage of oxygen in the carrier gas. Finally, the mechanism of α ‐H removal of methyl acetate through the activated oxygen was clarified. Abstract : The transformation of V 4+ and V 5+ in the presence of oxygen during the aldol condensation reaction plays a key role in the catalytic process. The mechanism of α ‐H removal of methyl acetate through oxidation with the activated oxygen ions was proposed and the reason of catalyst deactivation was investigated. Controllable synthesis catalysts were successfully applied to aldol condensation.